(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and subclinical characteristics and evaluate the surgical outcomes of ovarian teratomas treated at Nghe An Oncology Hospital in 2025. Subjects and methods: A cross-sectional descriptive study combining retrospective and prospective analyses was conducted on 126 patients histopathologically diagnosed with ovarian teratoma who underwent surgical treatment at Nghe An Oncology Hospital. Results: Ovarian torsion occurred in 4.8% of cases. The mean tumor size was 60.73 ± 29.56 mm (50-100 mm group accounted for 54%). Ultrasound risk stratification showed O-RADS 2 in 80.2%, O-RADS 3 in 11,9%, and O-RADS 4 in 7.9%. Histopathology revealed mature cystic teratomas in 96% and immature teratomas in 4%. Laparoscopy was the primary surgical approach (95.2%), with open surgery at 3.2% and conversion to open surgery at 2.6%. Ovary-sparing cystectomy was performed in 90.5%, salpingo-oophorectomy in 7.1%, and radical surgery in 2.4%. Postoperative complication rate was low (4%). Conclusion: Ovarian teratomas primarily affect women of reproductive age and follow an insidious clinical course. Laparoscopic cystectomy with ovarian tissue preservation is a safe, highly effective procedure associated with few complications.